Multiple esophageal duplication cysts in a toddler: A rare scenario - Parveen Kumar (Journal of Indian Association of Pediatric Surgeons, 2021)
The foregut duplication cysts are rare congenital malformation and are usually “solitary” midline noncommunicating mediastinal structures. We present a 2-year-old asymptomatic boy having multiple noncommunicating foregut cysts in the neck as well as the thorax.